Shidehara Kijuro and his time - Okazaki, Hisahiko 1930-2014 (Japan Library.)
Constitution of Japan is often described as a pacifist constitution for its Article 9 renouncing war and foreswearing war potential. Although this is usually attributed to starry-eyed idealists and steely-eyed realists in the occupation, both of which wanted to ensure Japan did not again challenge America's position, there is also a cast to be made for crediting Shidehara Kiju?ro? (1872-1951). Indeed, the case becomes even stronger if we think of the Constitution not so much as pacifist but more as internationalist--as evidenced in the Preamble's trusting in the justice and faith of the peace-loving peoples of the world and its belief that no nation is responsible to itself alone. For it was Shidehara who was the ultimate internationalist. Born to a middle-class family four years after the Meiji Restoration, he went to Tokyo Imperial University and from there to the civil service, ending up at the Ministry of Foreign Affairs. From there, history took him to a number of foreign capitals and historic international conferences on his way to the foreign ministership and after he became foreign minister. Serving as foreign minister under a succession of prime ministers, he developed and staunchly promoted what came to be called Shidehara diplomacy--a foreign policy stance of not intervening in China, respecting the Anglo-Japanese alliance, and adhering to what were put forward as universal values. Yet despite his steadfast championship, this internationalist stance was weakened by widespread discrimination against Japanese (e.g., in America's immigration laws) and fatally wounded by the Kwangtung Army's rogue aggression in China. He resigned as foreign minister in 1931, while retaining his seat in the House of Peers, and was tapped by the occupation to be Japan's first postwar prime minister, putting him in a position to influence the Constitution's drafting. Shidehara's was a principled life engagingly recounted in this informative biography by one of Japan's foremost diplomat-turned-historians."--Dust jacket.